STUDY OF RESISTANCE FOR RECENTLY MARKETED CARBAPENEM DRUG AMONG HOSPITALISED PATIENTS IN SANA'A, YEMEN - Alyahawi, Ali; Alkaf, Ali; Alnamer, Rashad; Alnosary, Taha (Universal Journal of Pharmaceutical Research, 2018)
Objective: Carbapenem resistance is a major and a future public health problem globally. It occurs mainly among Gram-negative bacteria. Meropenem is the recently marketed carbapenem drug in Yemen. However, recent emergence of carbapenem-resistant isolates has become a major healthcare concern. The current study was designed to estimate the prevalence of meropenem resistance among hospitalised patients in Sana'a, Yemen. Methods: The study was performed at a local hospital in Sana’a, Yemen. The records of Meropenem susceptibility were taken for hospitalised patients. A total of 443 Meropenem susceptibility samples were collected from August, 2017 to July, 2018. The meropenem susceptibility was studied against several isolated pathogens. Results: Out of 443 study sample, 316 (71.3%) were meropenem sensitive isolates and 25.3% of samples were resistant. The Escherichia coli isolates were observed in 27.5% of sample, followed by Pseudomonas aeruginosa (19.6%). 36.4% of total meropenem sensitive isolates (115/316) were Escherichia coli. 82.4% (42/51) of Klebsiella pneumonia isolates were meropenem sensitive and 32.2% (28/87) of Pseudomonas aeruginosa were meropenem resistance. In the present study, 34.5% (109/316) of meropenem sensitive isolates were from blood cultures, followed by sputum cultures (23.7%; 75/316). However, 58% (65/112) of sputum culture isolates were meropenem resistance. Conclusion: This study concluded that the percentage of resistance to meropenem was high (25.3%) and cannot be neglected. Continued surveillance to closely monitor trends as well as infection control and antibiotic stewardship activities are necessary to preserve treatment options. A more careful monitoring for use of broad-spectrum antibiotics should be instituted. Peer Review History: Received 26 July 2018; Revised 7 September; Accepted 23 October, Available online 15 November 2018 Academic Editor: Dr. Jennifer Audu-Peter , University of Jos, Nigeria, drambia44@gmail.com Reviewer(s) detail: Prof. Dr. Hüsniye Kayalar , Ege University, Turkey, husniyekayalar@gmail.com Noha El Baghdady , MTI University, Cairo, Egypt, nohasalah21@yahoo.com